Pengaruh Samsat Keliling Dan E-Samsat Terhadap Kualitas Pelayanan Pajak Kendaraan Bermotor: (Studi Kasus Pada Wajib Pajak di Samsat Kota Tangerang) - Aas Astriyah; Erliana Erliana; Linawati Linawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to: 1) Examine and analyze the effect of Mobile Samsat services on the quality of motor vehicle tax services, 2) Analyze the effect of E-Samsat services on the quality of motor vehicle tax services, and 3) Evaluate the simultaneous effect of Mobile Samsat and E-Samsat services on the quality of motor vehicle tax services in Tangerang City. This research uses a quantitative approach with a survey method. The population consists of motor vehicle taxpayers in Tangerang City, and the sample of 100 respondents is determined using the Lemeshow formula. Data are collected through a structured questionnaire with a Likert scale and analyzed using multiple linear regression with SPSS version 29. The results show that: 1) Mobile Samsat has a positive and significant effect on service quality (p < 0.05), 2) E-Samsat has a positive and significant effect on service quality (p < 0.05), and 3) simultaneously, both independent variables significantly affect service quality (F-statistic p = 0.000). The Adjusted R² value indicates that the model explains a substantial portion of the variation in service quality. These findings suggest that improving the infrastructure of Mobile Samsat and optimizing E-Samsat operations can enhance accessibility, satisfaction, and taxpayer compliance in Tangerang City.